Digitaler Faschismus und digitaler Kapitalismus - Fuchs, Christian (tripleC: Communication, Capitalism & Critique)

The Futures of Digital Democracy Survey (FDDS): Report and Analysis - Fuchs, Christian; Museba, Joel; Friesch, Kevin

Rewriting Ontology-Mediated Property Graph Queries into GQL - Löhnert, Bianca; Augsten, Nikolaus; Okulmus, Cem; Ortiz, Magdalena (Proceedings of the 35th International ACM Conference on Knowledge and Information Management (CIKM 2026))

Prospective Associations Between Morphological Awareness and Children’s (Written) Language Skills: A Systematic Meta-Analytic Review of Longitudinal Studies - Bodynek, Joanna; Gaigulo, Dana; Mayer, Andreas; Jonas, Kristina (Educational Research Review)

Orthographie im Längsschnitt. Zur Rolle schriftstruktureller Komplexität bei Wortschreibungen. - Drepper, Laura; Topalovic, Elvira (Zeitschrift für germanistische Linguistik (ZGL))
Empirical studies of the past three decades examining children’s written language acquisition suggest that students are sensitive to the acquisition of structural patterns even before the explicit teaching of orthographic phenomena. It can be assumed that structural complexity of the orthographic phenomena could be important for school acquisition processes. In the longitudinal study „Development of (Spelling) Writing from Primary to Secondary School“, the acquisition of orthographic regularities (e. g., <h> spellings, double consonance) was documented for the first time throughout the entire primary school period. In this article, we focus on word spellings, which were assessed using picture-word writing at a total of 10 time points (three assessment points in the 1st and 2nd grades and two assessment points in the 3rd and 4th grades). The subject of the analysis are the language data of children who participated in all 10 time points (n=77). The data analysis aims to answer the question of the order in which orthographic regularities are acquired. In accordance with the above-mentioned assumption, the role of the structural complexity in the acquisition order will also be examined. To this end, the results will first be examined descriptively by calculating means and standard deviations. Subsequently, inferential statistical methods for comparing means (ANOVA and t-test) will be used to test the significance of the acquisition processes. The results show that children acquire the orthographic regularities in the following order: <e> spellings in reduction syllables, syllable-initial <h> in syllabic spellings, morphological spellings in consonantal derivation, <ie> spellings in main syllables, morphological spellings in vocalic derivation, and double consonance in syllabic spellings. Furthermore, double consonance and the syllable-initial <h> are correctly realized first in syllabic and then in morphological spellings. Based on the results, the importance of structural complexity for spelling acquisition, for example with regard to syllabic and morphological spellings, as well as the implications of the results for teaching practice are discussed.

Technical Analysis of the Geedge Networks Firewall Source Code Leak - Ablove, Anna; Walker, Johnnie; Wolin, Ben; Niere, Niklas; Graf Lange, Felix; Ortwein, Aaron; Huremagic, Armin; Priyanka, Richa; Zohaib, Ali; Sheffey, Jade; Heitmann, Nico; Halderman, J. Alex; et al.
In September 2025, over 100K internal documents (including code, communications, etc.) from Geedge Networks, a Chinese DPI company with ties to the Great Firewall of China, were leaked to the public. In this paper, we analyze the source code from this leak, focusing on Geedge Networks’ flagship product, the Tiangou Secure Gateway (TSG) firewall. Working across multiple repositories, we successfully build and run a local copy of TSG—revealing key aspects of its architecture, including the protocols it is capable of parsing and the format of blocking rules used to censor sites, proxies, and other resources. Finally, we extract several fingerprints from TSG, including custom random number generators and parsing idiosyncrasies that allow us to identify its use and similar deployments in the Great Firewall of China. This is the first time that the source code of a commercial DPI has been leaked, and our work is the first code analysis of a core firewall component used in national censorship infrastructure. This unprecedented investigation offers insights that can assist circumvention developers and Internet security researchers in further understanding the capabilities and limitations of modern censorship technology.

On Russia’s Early Introduction of QUIC SNI Censorship - Heitmann, Nico; Niere, Niklas; Graf Lange, Felix; Somorovsky, Juraj
Governments around the world limit free access to information through Internet censorship. With the rising adoption of the QUIC protocol, these censors have been forced to evolve their systems. Russia introduced sweeping changes to its censorship after its full-scale invasion of Ukraine, including completely blocking international QUIC connections. However, after this broad filter was identified in 2022, Russian QUIC censorship received little attention: The current state of QUIC censorship by TSPU devices is largely unknown. In this paper, we provide a timeline of Russian QUIC censorship and detail its current state. We identify that Russian TSPU devices switched to SNI-dependent QUIC censorship on a large scale between May 2022 and July 2023, a fact that went largely unnoticed for three years. While the GFW was previously thought to be the first censor with broad SNI-dependent QUIC censorship, we highlight that Russian TSPU devices broadly adopted SNI-dependent QUIC censorship at least nine months before the GFW. We consider this an indicator of the TSPU devices’ flexibility and of Russia’s willingness to invest in strict and up-to-date censorship.

When Trying Harder Helps: Effort Instructions Affect Performance in Complex Motor Tasks - Böer, Nils Tobias; Steinborn, Michael B.; Weigelt, Matthias; Güldenpenning, Iris (Abstracts of the 68th Conference of Experimental Psychologists)
Keywords: effort; try-harder instruction; deception; sport psychology; action and perception

From interference to priming? Reinterpreting the head-fake effect in basketball through continuous measurements - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Strategic adaptations to deceptive actions in sports: The anticipation-response-inhibition-accuracy trade-off - Wickemeyer, Carolin; Weigelt, Matthias; Güldenpenning, Iris (Journal of Sport and Exercise Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 68th Conference of Experimental Psychologists)

Rapid chase or continuous flow of information? Visual-motor processing of head fakes in basketball - Güldenpenning, Iris; Schulze Frielinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

The role of domain-specific expertise on response inhibition in the basketball-specific ARI-task - Wickemeyer, Carolin; Güldenpenning, Iris; Meyer, Johannes; Klatt, Stefanie; Weigelt, Matthias (Abstracts of the 58th Annual Conference of the German Association of Sport Psychology)

Efficient Silicon Nitride Quantum Interconnect for Intrinsic Silicon Nitride Single-Photon Emitters - Farheen, Henna; Chen, Yuheng; Chen, Peigang; Maan, Pranshu; Peana, Samuel; Senichev, Alexander; Shalaev, Vladimir M.; Boltasseva, Alexandra; Förstner, Jens; Kildishev, Alexander V. (IEEE Journal of Selected Topics in Quantum Electronics)
Keywords: tet_topic_opticalantenna

Predictors of primary school students’ prosocial behaviour toward peers with social-emotional difficulties in inclusive education: Insights from the Theory of Planned Behaviour. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Löper, Marwin Felix; Knickenberg, Margarita; Hellmich, Frank

Teachers’ conceptualizations of social-emotional competencies in cooperative learning: Insights from inclusive primary school classrooms. Individual Paper Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Knickenberg, Margarita; Funk, Michael; Casamassima, Gianna; Löper, Marwin Felix; Hellmich, Frank

Social and emotional competencies for cooperative learning in inclusive primary education: A project overview. Poster Presentation. EARLI SIG 15 Biennial Conference 2026 ‘Special Educational Needs’. “Research methodological approaches bridging special educational needs”. - Casamassima, Gianna; Funk, Michael; Knickenberg, Margarita; Löper, Marwin Felix; Grosche, M.; Zimmer, L.; Grüßing, M.; Wess, N.; Hellmich, Frank

Prokrastination: Erkennen, Verstehen, Reduzieren

Photovoltaik Alles-in-einem-Band für Dummies - Krauter, Stefan; Froitzheim, Armin

Variationen eines Systemalptraums: Postmigrantische Befindlichkeiten in Burhan Qurbanis "Berlin Alexanderplatz" und Visar Morinas "Exil" - Morrien, Rita (Grenz(über)fälle und Grenzgänge: Literatur, Kunst und gesellschaftliche Dynamiken ab 2000)
Sowohl in Burhan Qurbanis "Berlin Alexanderplatz" als auch in Visar Morinas "Exil" werden Paradoxien der postmigrantischen Gesellschaft mittels einer filmischen Ästhetik des Traums reflektiert. In Qurbanis radikaler Aktualisierung von Döblins Berlin "Alexanderplatz" ist die Hauptfigur ein Schwarzer Geflüchteter, der in Deutschland auf einen Neuanfang als ‚anständiger Mensch‘ hofft. Morinas Exil erzählt die Geschichte eines scheinbar vorbildlich integrierten Migranten, der sich plötzlich als Opfer von Rassismus erlebt. Die Filme werden hier als Variationen eines Systemalbtraums gelesen, weil in beiden Fällen die kollektiven Ängste der Dominanzgesellschaft vor dem ‚parasitären Anderen‘ und die Idee der pluralen Demokratie zur Kollision gebracht werden.
Keywords: Postmigrantischer Film; Traumästhetik; Burhan Qurbani; Berlin Alexanderplatz; filmische Adaption; Visar Morina